PURPOSES, PROBLEMS AND SUPPORT OF THE STRATEGIC PLAN OF INTRODUCTION OF INFORMATION TECHNOLOGIES IN THE CONCEPT OF UNIVERSITY DEVELOPMENT - Spivakovsky О.В.; Kravtsov Г.М. (Journal of Information Technologies in Education (ITE), 2012)
Results of designing, development and realization of the strategic plan of introduction of information technologies according to the concept of the Kherson State University development are presented.